2021
DOI: 10.1021/acs.estlett.1c00476
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Classic Phthalates: Occurrence of Multiple Emerging Phthalate Alternatives and Their Metabolites in Human Milk and Implications for Combined Exposure in Infants

Abstract: Because of the recognized toxicity and legislative regulation of classic phthalates (PAEs), the manufacture and use of PAE alternatives have rapidly grown. However, lactational exposure to these emerging replacement chemicals remains unknown. In this study, 11 classic PAEs, 14 emerging PAE alternatives, and 24 of their metabolites were comprehensively investigated in human milk from China. Except for nine detectable PAEs, nine of the 14 emerging PAE alternatives, including three (1,4-DEHCH, 1,2-DEHCH, and DEHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The total concentration of the 11 detectable TA-UVFs (∑ 11 TA-UVFs) ranged from 570 to 14,000 pg/mL, with a median of 1350 pg/mL. Compared to that of other emerging chemicals of concern reported in breast milk in the last five years (Figure S4), the median level of ∑ 11 TA-UVFs was lower than those of photoinitiators (11,082 pg/mL, the U.S.) and synthetic phenolic antioxidants (16,700 pg/mL, China), comparable to those of melamine and its derivatives (1400 pg/mL, the U.S.) and nonphthalate plasticizers (1870 pg/mL, China) but 1 order of magnitude higher than those of per- and polyfluoroalkyl substances (121 pg/mL, the U.S.) and bisphenol analogues (60.5 pg/mL, China) . Notably, the comparisons indicate that TA-UVFs are an important class of previously unrecognized pollutants present in breast milk.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The total concentration of the 11 detectable TA-UVFs (∑ 11 TA-UVFs) ranged from 570 to 14,000 pg/mL, with a median of 1350 pg/mL. Compared to that of other emerging chemicals of concern reported in breast milk in the last five years (Figure S4), the median level of ∑ 11 TA-UVFs was lower than those of photoinitiators (11,082 pg/mL, the U.S.) and synthetic phenolic antioxidants (16,700 pg/mL, China), comparable to those of melamine and its derivatives (1400 pg/mL, the U.S.) and nonphthalate plasticizers (1870 pg/mL, China) but 1 order of magnitude higher than those of per- and polyfluoroalkyl substances (121 pg/mL, the U.S.) and bisphenol analogues (60.5 pg/mL, China) . Notably, the comparisons indicate that TA-UVFs are an important class of previously unrecognized pollutants present in breast milk.…”
Section: Resultsmentioning
confidence: 95%
“…The research protocol was approved by the ethics committee of Jinan University. Detailed sampling details can be found in the Supporting Information (SI) and our previous work …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in a reporter assay, DINCH did not show any effect on the activity of human nuclear receptors ERα, ERβ, AR, PPARα, and PPARγ (TRα not tested), but endogenous primary and secondary metabolites of DINCH resulted in activation of all these receptors [ 60 ]. Epidemiological studies have shown that DINCH metabolites were detected alongside phthalate metabolites in human urine samples worldwide [ 14 ]. Relating to thyroid function, urinary levels of a DINCH metabolite (MOiNCH) were positively associated with total T3 concentrations and a lower total T4/total T3 ratio in women [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, DEHP and other phthalate plasticizers tend to leach out of PVC products over a period of time due to their non-covalent binding with the polymer matrix, leading to their release and ubiquitous presence in the environment [ 9 , 10 , 11 , 12 , 13 ]. As a result, phthalate compounds gain access to human and animal systems and are known to cause hepatotoxic, carcinogenic, reproductive, developmental, neurotoxic, growth-associated, and endocrine system problems, including thyroid problems [ 2 , 14 , 15 ]. These adverse effects have prompted the European Union and the United States to impose restrictions on the use of several phthalates, including DEHP in many children’s and medical products [ 16 ].…”
Section: Introductionmentioning
confidence: 99%